Photocatalytic degradation of organic dyes by UV light, catalyzed by nanostructured Cd-doped ZnO synthesized by a sonochemical method - Anukorn Phuruangrat (2018)
© Springer Science+Business Media Dordrecht 2015. ZnO and Cd-doped ZnO photocatalysts were successfully synthesized by use of a sonochemical method. The as-synthesized ZnO and Cd-doped ZnO photocatalysts were characterized by X-ray diffraction, Raman spectroscopy, Fouriertransform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, Brunauer-Emmett-Teller analysis, inductively couple plasma-optical emission spectrometry, and X-ray photoelectron spectroscopy. The assynthesized ZnO and Cd-doped ZnO photocatalysts were pure wurtzite hexagonal ZnO phase. The Raman-active E2H mode of ZnO, located at 437 cm-1, corresponded to the characteristic band of the hexagonal wurtzite phase. The photocatalytic activity of the pure ZnO and Cd-doped ZnO photocatalysts was investigated by studying the degradation of methylene blue (MB) and methyl orange (MO), in solution, under UV irradiation. Compared with pure ZnO, 3 % Cd-doped ZnO reduced the amounts of MB and MO by 65 % and 45 %, respectively, within 300 min. The results indicated that Cd dopant substantially increased the photocatalytic activity of ZnO.